Política de inovação da década de 2000: produtividade e inovação - Calzolaio, Aziz Eduardo (Cadernos do Desenvolvimento, 2019)
RESUMO O objetivo deste trabalho é comparar a performance das capacitações tecnológicas e da produtividade das firmas que receberem benefícios da política de inovação com as que não receberam esse encorajamento durante a década de 2000. Para tanto, procedeu-se à construção e aferição de diversos indicadores representativos das capacitações tecnológicas, bem como calculou-se a produtividade do trabalho, por meio da técnica Shift-Share, para dois grupos de empresas: um usuário da política de inovação e outro não usuário de tal incentivo público. Sendo que as fontes de dados foram tabulações especiais da Pesquisa de Inovação Tecnológica e da Pesquisa Industrial Anual, ambas do IBGE. Concluiu- -se que as empresas usuárias da política de inovação melhoraram suas capacitações tecnológicas e tiveram uma produtividade do trabalho comparativamente maior. PALAVRAS-CHAVE: Política de Inovação; Produtividade; Atividade de Inovação. ABSTRACT This article seeks to compare the performance, in terms of technological capacity and productivity gains, of companies that received different benefits from innovation policies adopted in Brazil, with that of companies that did not receive such benefits during the first decade of this century. To this end, a collection and assessment of different indicators representing technological progress was made, and labour productivity was calculated using the Shift-Share technique in the case of two groups of companies: one that took advantage of the available incentives of public innovation policies, and the other that didn’t. The source of data came from the IBGE, in the form of its Survey of Technological Innovation and Annual Industrial Research tables. The conclusion was that the companies making use of the innovation policy incentives did indeed improve their technological capacities and saw their labour productivity rise more when compared to those that didn’t. Key-words: Innovation Policies; Productivity; Innovation Activity. JEL Classification 025. O38. O47.